Supplementation of Carrot (Daucus carrota) as Natural Source of Beta-carotene prepared by Several Methods in Feed to Increase Blue Colour of Freshwater Crayfish Red Claw (Cherax quadricarinatus) - Woro H. Satyantini; A. Shofy Mubarak; A. Taufiq Mukti; Ninin C (Jurnal Akuakultur Indonesia)
Red claw (Cherax quadricarinatus) is one kind of freshwater crayfish that can cultured as consumption or ornamental fish commodities.  The colour of body was important character for performance of red claw as ornamental fish commodity.  Red claw with blue body colour is more expensive than brown.  The purpose of  this experiment was to know the influence addition of carrot with several methods in feed on blue colour  of freshwater crayfish red claw and which was the best preparation method to increase blue colour of freshwater crayfish red claw. The experiment used Completely Randomized Design with four treatments: A (control), B (extract), C (juice) and D (shreeded) of carrot with 45 ppm dose and five time replicates.  Data was analysed with Kruskal-Wallis and continued with Z test. Result of the experiment was showed that addition of carrot as natural source of beta-carotene with several preparation in feed increase significantly (P